Occurrence of Ecto- and Endo-mycorrhizae with the Roots of Casuarina Equisetifolia in Various Soil Types - Singh, C. S.; Kapoor, Anjana; Rana, J. P. S. (Indian Forester, 1998)
Out ofthe fourteen samples collected from various locations in India, VA-mycorrhizal formation was observed in nine soil samples. External mycelial (ecto-mycorrhizae) association were also recorded in ten samples. Harting net and intercellular mycelial colonization with the root under the situation were not observed. In few soil samples plant roots were colonized with both endomycorrhizal and ecto-mycorrhizal fungi, whereas in five soil samples only endo-mycorrhiza and in three ecto-mycorrhiza alone was observed. Only in one soil sample no mycorrhizal association was noted study indicate the presence/absence of both type of mycorrhiza forming fungi in the soil. Maximum VAM root colonization was observed in Jabalpur soil, indicating the presence of potent VAM fungal species. Higher ecto-mycorrhizal colonization was recorded in Baroda soil sample.